PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER MENGGUNAKAN SYSTEM APPLICATION AND PRODUCT DATA PROCESSING (SAP) TERHADAP KINERJA INDIVIDU PADA PT. TIGARAKSA SATRIA TBK CABANG BANJARMASIN - Ferra Maryana; Saidatun Nisa (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, This study aimed to give empirical evidences about the effect of accounting information system based on computer using system application data processing quality to individual performance on PT Tigaraksa Satria Tbk Banjarmasin Branch. The dependend variable was individual performance and the independent variable was accounting information system quality. The population in this study was 30 employees of PT Tigaraksa Satria Tbk Banjarmasin Branch. The data collected from the output of questionnaires which gived to the respondents. The samples technique used total sampling with 30 employees as respondent. The study gived empirical evidences that system quality (using SAP) had positive effect to individual performance on PT Tigaraksa Satria Tbk Banjarmasin Branch.